2019
DOI: 10.20517/2394-4722.2019.0010
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies to the exon 18 encoded moiety of NCAM

Abstract: Aim: Exon 18 expression of NCAM has been recognized as a biomarker for small cell lung cancer (SCLC). To use this finding for an improved diagnosis of SCLC and personalized treatment of patients, techniques to identify and quantitate E18, the exon 18 encoded protein moiety of NCAM, are needed. We developed three monoclonal antibodies for this purpose. Methods: The his-tagged E18 antigen was expressed in E. coli and, after purification, used to immunize mice. Hybridoma's were isolated by standard procedures and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Human tumor cell lines, as well as 31 primary SCLCs have been reported to express exclusively the NCAM 140 variant. However, other studies have also demonstrated the presence of the NCAM 180 variant in SCLC and/or SCLC cell lines and even shown its specificity for these tumors [19,[129][130][131]. An additional NCAM 95 variant is also present in SCLC tumors and cell lines [129].…”
Section: Ncam1mentioning
confidence: 95%
See 1 more Smart Citation
“…Human tumor cell lines, as well as 31 primary SCLCs have been reported to express exclusively the NCAM 140 variant. However, other studies have also demonstrated the presence of the NCAM 180 variant in SCLC and/or SCLC cell lines and even shown its specificity for these tumors [19,[129][130][131]. An additional NCAM 95 variant is also present in SCLC tumors and cell lines [129].…”
Section: Ncam1mentioning
confidence: 95%
“…By definition, a tumorlet > 5 mm in diameter is termed carcinoid [128]. Although they were originally described as being of benign nature, tumorlets behave like carcinoids, are reported to cause Cushing's syndrome [22,130,131], and may metastasize to lymph nodes [20,130] or even distantly [22]. Reactive PNEC hyperplasias resulting from chronic pulmonary disease can also progress to a tumorlet phase.…”
Section: Precursor Lesionsmentioning
confidence: 99%